PENGARUH PENAMBAHAN TEPUNG REBUNG (DENDROCALAMUS ASPER) TERHADAP MUTU NUGGET IKAN BIJI NANGKA (UPENEUS MOLUCCENIS) - Retno_rizki Retno_rizki; desmelati_desmelati desmelati_desmelati; suparmi_suparmi suparmi_suparmi (Fakultas Perikanan dan Kelautan, Universitas Riau, 2018)
The purpose of this research is to determine the effect of adding bamboo shoots (Dendrocalamus asper) flour to the quality of goatfish (Upeneus moluccenis) nugget. The treatment is with total tapioca flour used 75 g with the addition of bamboo shoot flour which consists of 4 levels ie NO (0% bamboo shoots flour), N1 (5% bamboo shoots flour), N2 (10% bamboo shoots flour), N3 (15% bamboo shoots flour). Based on the research, the effect of the addition of bamboo shoots flour to goatfish nugget quality was significantly affect to the organoleptic value, moisture, ash, protein, fat, and crude fiber content. The result of the study on N3 treatment was the best treatment with characteristics: light brown appearance (7.27), very specific of goatfish odor (7.32), savory taste (7.32), solid and compact texture (7.56 ) and the chemical values of moisture, ash, protein, fat, and carbohydrate content are 40.79%, 2.05%, 10.50%, 1.02%, 25.23%, 20. 43%, respectively.